2019
DOI: 10.1007/s00381-019-04129-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of tethered cord syndrome—comparing the results of surgeries with and without electrophysiological monitoring

Abstract: Purpose To compare the short-and long-term outcomes after surgical treatment of tethered cord syndrome with and without electrophysiological monitoring. Method We collected the preoperative data of 102 tethered cord surgeries of 91 patients. We compared the outcomes regarding the presence of intraoperative electrophysiology, the types of surgeries and the preoperative neurological condition. We also analysed the long-term outcomes in the cases of 69 patients. Results We found that intraoperative electrophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…15,51 This approach improves surgical outcomes and reduces the likelihood of postoperative recurrence. 52,53 Ultrasound can also assist in early TCS diagnosis, especially during pregnancy, due to its rapid and noninvasive nature. 54,55 However, after closure of the spinal canal, ultrasound becomes less effective in accurately detecting the conus position given its limited ability to penetrate bone.…”
Section: Examinationmentioning
confidence: 99%
“…15,51 This approach improves surgical outcomes and reduces the likelihood of postoperative recurrence. 52,53 Ultrasound can also assist in early TCS diagnosis, especially during pregnancy, due to its rapid and noninvasive nature. 54,55 However, after closure of the spinal canal, ultrasound becomes less effective in accurately detecting the conus position given its limited ability to penetrate bone.…”
Section: Examinationmentioning
confidence: 99%
“…In this study, all of the patients showed congenital developmental malformations and were newly diagnosed patients. The imaging manifestations of this disease are varied, and mainly include a low spinal cord, myelolipoma, lipomyelomeningocele/meningocele, syringomyelia, diastemastomyelitis, spina bifida, scoliosis, and fur sinuses (3)(4)(5)(6). Complex TCS (C-TCS) is accompanied by complex and varied spinal cord manifestations and nerve root adherents along with severe lumbosacral coccygeal vertebrae deformities (7).…”
Section: Introductionmentioning
confidence: 99%
“…In childhood, symptoms are often worsening during growth spurts; while among adults, trauma or stretching can elicit the complaints. 4 Considering TCS has a progressive course, surgical treatment cannot be avoided. In childhood, the diagnosis of tethered cord alone should be an indication for surgery for avoiding neurological deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…In childhood, the diagnosis of tethered cord alone should be an indication for surgery for avoiding neurological deterioration. 4,5 Stabilization of neurological situation is achieved by untethering. Early intervention appears to result in a much greater recovery.…”
Section: Introductionmentioning
confidence: 99%